ELEMENTS OF THE STUDY OF SOCIAL AND MARKET DEMAND OCCUPATIONAL CAREER ACCOUNTING FOR NATIONAL ACCREDITATION PURPOSES - Flores Konja, Adrián Alejandro (2013)
The article presents the partial results and conclusions of the research entitled: “Elements of the study of social and market demand occupational career accounting for national accreditation purposes”, running in this period 2013. The study has been expressly required by the CONEAU Quality Model. However, its importance transcends the formal aspect of the requirement for accreditation, being important for the process of continuous improvement in the School of Accounting. The Ministry of Education reports a problem of relevance in the Peruvian University, as presented by one side do not have careers that applicants and on the other races with many graduates , many of them can not be absorbed by the job market ‘s own the race, this study allows focusing both. For the Accounting Career is part of a positive assessment of both social demand careers offered by our School of Accounting and the rapid absorption of our graduates for the job market. The study design will allow us to corroborate, maintain and improve the advantage achieved by our faculty.